Counterregulatory response to hypoglycemia during a hypoglycemic clamp in people with type 2 diabetes treated with tirzepatide - Pieber, Thomas R.; Svehlikova, Eva; Urva, Shweta; Haupt, Axel; Zhou, Chunmei; Coskun, Tamer; Höller, Vera; Fluhr, Gabriele; Karanikas, Chrisanthi A.; Milicevic, Zvonko; Pratt, Edward John (Frontiers in Endocrinology, 2025)
IntroductionTo evaluate counterregulatory hormonal responses during a hypoglycemic clamp with tirzepatide.MethodsParticipants with type 2 diabetes (N=42) were randomized to tirzepatide (15 mg) or placebo for 12 weeks in a crossover design, with a wash-out period of 8–10 weeks. The primary objective was the change in glucagon response during clamp-induced hypoglycemia from plasma glucose (PG) 100 mg/dL to nadir PG (45 mg/dL). Secondary measures were changes in responses of other counterregulatory hormones during clamp-induced hypoglycemia. Time to recovery from the nadir to 72 mg/dL and hypoglycemic symptom scores using the 7-point Edinburgh Hypoglycemia Symptom scale were also assessed.ResultsAt 12 weeks, HbA1c change from baseline was -1.5% with tirzepatide versus +0.5% with placebo. During induced hypoglycemia, mean PG levels at nadir were 44.5 mg/dL with tirzepatide and 47.5 mg/dL with placebo. Increases in glucagon from PG 100 mg/dL to nadir PG and during recovery from the nadir to 72 mg/dL did not differ between treatments (p=0.756 and p=0.565, respectively). Growth hormone and adrenaline responses did not differ between treatments. Cortisol and noradrenaline responses were delayed with tirzepatide, consistent with lower hypoglycemic symptom scores at nadir observed during tirzepatide treatment periods versus placebo (p=0.007). The proportion of participants aware of hypoglycemia did not differ between treatments.DiscussionThe response of the key counterregulatory hormone glucagon to induced hypoglycemia was maintained with tirzepatide.Clinical trial registrationClinicalTrials.gov, identifier NCT04050553.